2003
DOI: 10.1159/000074649
|View full text |Cite
|
Sign up to set email alerts
|

Skp2 and Jab1 Expression Are Associated with Inverse Expression of p27<sup>KIP1</sup> and Poor Prognosis in Oral Squamous Cell Carcinomas

Abstract: Previous studies have shown that low levels of p27KIP1, an inhibitor of G1 cyclin-dependent kinases (CDK), are associated with high aggressiveness and poor prognosis in a variety of cancers. Decreased levels of p27KIP1 are caused, at least in part, by an acceleration of degradation with Skp2 (S-phase kinase-associated protein 2) and Jab1 (Jun activation domain-binding protein 1). This investigation was undertaken to examine whether the Skp2 and Jab1 expression is correlated with p27K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
54
0
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 21 publications
8
54
0
11
Order By: Relevance
“…Further statistical analysis revealed that amplification and overexpression of SKP2 were significantly associated with positive lymph node metastasis and tumor stage. Immunohistochemical analyses by other investigators also revealed that overexpression of SKP2 was associated with lymph node metastasis in oral squamous cell carcinoma (19) and laryngeal squamous cell carcinoma (20). Significantly inverse correlation between SKP2 and p27 expression was found in ESCC, which was concordance with reports in other tumors (16,17,21).…”
Section: Discussionsupporting
confidence: 72%
“…Further statistical analysis revealed that amplification and overexpression of SKP2 were significantly associated with positive lymph node metastasis and tumor stage. Immunohistochemical analyses by other investigators also revealed that overexpression of SKP2 was associated with lymph node metastasis in oral squamous cell carcinoma (19) and laryngeal squamous cell carcinoma (20). Significantly inverse correlation between SKP2 and p27 expression was found in ESCC, which was concordance with reports in other tumors (16,17,21).…”
Section: Discussionsupporting
confidence: 72%
“…13,30 To our knowledge, only one previous study has been published on the expression of p27 kip1 and Jab1 proteins in systemic anaplastic large cell lymphoma (ALCL), and that report also showed Jab1 and p27 kip1 expression were inversely correlated. 15 In the current study, 71.55% NHLs showed Jab1 positive expression and was significantly associated with the clinical stage. Therefore, these results suggested that Jab1 protein, as a negative regulator of p27 kip1 , might contribute to the progression of NHLs.…”
Section: Discussionsupporting
confidence: 48%
“…Jun activation domain-binding protein 1 negatively regulate p27 kip1 in non-Hodgkin's lymphomas squamous cell carcinomas, 15 etc. George et al 16 found that p27 kip1 was absent or expressed at low levels in most systemic anaplastic large cell lymphoma (ALCL) and inversely correlated with Jab1.…”
Section: Research Papermentioning
confidence: 99%
“…Many studies have reported that JAB1 is overexpressed in different types of cancers. The overexpression of JAB1 is inversely associated with p27 levels and correlates with poor prognosis (Kouvaraki et al, 2003;Shintani et al, 2003;Osoegawa et al, 2006).…”
mentioning
confidence: 99%